(untitled) (Heritage, 2022)
The paper analyzes Ivo Andrić’s literary work in terms of the culture of forgetting. The culture of forgetting is not comprehended as an antithesis of the culture of remembrance, neither as a political or ideological construct, but as a specific Andrić’s sensibility, that shows the ubiquitous wish for being overwhelmed by non-existence, preserved in disappearance, fused with oblivion in silence. Therefore, some aspects of Andrić’s literary work in the light of the culture of forgetting have been emphasized: 1) silence as a form of forgetting; 2) theatre stage and play as strategies of forgetting; 3) the special place of snow as a motif in Andrić’s literature. Special attention is given to Andrić’s short stories: The Bridge on the Žepa (Most na Žepi), Aska and the Wolf (Aska i vuk), Play (Igra), Children (Deca).